Pengaruh Kekeruhan Atmosfir Terhadap Kesetimbangan Radiasi Matahari - Tuti Budiwati; Rukmi Hidayati; Iis Sofiati (Indonesian Journal of Physics, 2003)
The solar radiation intensity of 500 nm wavelength is measured by Eko-Sun photometer model MS-120 on clear days. The magnitude of atmospheric turbidity coefficient plays important role in increasing or decreasing temperature near earth’s surface. The atmospheric turbidity coefficients at wavelength of 500 nm in Bandung had range from 0.25 to 1.20 during dry season from June to October from 1996 to 1998. The decrease of atmospheric turbidity coefficient value of 0.015 was based on different value of atmospheric turbidity coefficient from 0.461 to 0.446 in 1996 and 1998 which resulted in increasing temperature near earth’s surface about 0.49oC.